Neighborhood-Level LCA and Hotspot Analysis of Embodied Emissions of a New Urban Area in Reykjavík - Hjördís Sóley Sigurðardóttir; Jukka Heinonen; Ólafur Ögmundarson; Áróra Árnadóttir (Sustainability, 2023)
The built environment sector causes significant climate change impacts, which indicates an opportunity for the sector to be of great importance in reducing its global impact. The main strategy has focused on urban density and transport as well as studying the emissions caused by buildings with life-cycle assessments (LCAs). However, a holistic approach is often missing, where life-cycle environmental impacts are assessed, and goals are considered at the planning stage. This study proposes LCA on a neighborhood scale for a holistic approach and to identify how LCA can be used to reduce impacts when designing and for decision-making at the planning stage. The focus is on the pre-use phase because that phase has been proven to cause a significant spike in carbon emissions when considering the near future and is crucial in reaching climate goals. The study case is a new neighborhood plan in Reykjavík, Iceland. The assessment focuses on the climate change impact of building a new neighborhood. The study identifies materials as a key factor. It demonstrates how the total emissions of the neighborhood are reduced when more environmentally friendly materials are replaced by traditional ones. It reduces GHG emissions by up to 40% in total.